Effects of Exer–Gaming on Balance and Gait in Parkinson’s Patients - Shahbaz Qayyum, Zeest Hashmi, Shoaib Waqas, Muhammad Tariq, Muhammad Waqas Mughal, Mohsin Tanvir (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Parkinson’s disease is the most progressive disorder of the nervous system. The four major features of Parkinson’s disease are tremors at rest, rigidity, hypokinesia, and postural instability. Aim: To evaluate outcomes of virtual based games in patients suffering from Parkinson disease and their effects on balance and gait training. Methodology: It was a 6-month randomized clinical trial study. 16 patients were taken for the study after the sample was calculated through G power analysis software. According to the inclusion criteria, patients between age 40 and 65, both males and females, with stage 1, 2, or 3, patients with gait and balance disorders were taken for study. Patients not fulfilling the criteria were excluded. Group 1 received an exercise gaming treatment plan which included wii perfect ten balances, wii-skiing, and wii-cycling. Patients received three sessions per week for two months. Each treatment session lasted 50 minutes with two minutes of rest between each exercise. Group 2 received a conventional treatment plan which included balance training, gait training, stretching and strengthening exercises. Patients received three sessions per week for two months. Results: The mean difference of UPDRS was 87.25 before treatment and 81.12 after treatment in group 1, while it was 86.25 before and 86.00 after treatments. The dynamic gait index was 14.12 before treatment and 19.12 after treatment in group 1. The average group score was 14.12 before treatment and 16.21 after treatment. Conclusion: The study concluded that Exer-games have shown a significant impact on the balance and gait of Parkinson’s patients as compared to conventional physical therapy alone. Keywords: Gaming, UPDRS, DGI, Parkinson, Postural Instability